Pengakuan Hak Ulayat Tanah Baduy dalam Lintasan Sejarah: Kolonialisme (Agrarische Wet) Menuju Kebijakan Perda - Aulia Uswatun Hasanah; Rezza Fauzi Muhammad Fahmi; Nur Bibat Andiatna; Siti Rahmawati; Dewi Zahra Komala (Universitas Galuh, 2026)
This study analyzes the transformation of the recognition of Baduy customary land rights from colonial state domination to constitutional recognition in modern Indonesia (1870–2022). Employing a historical method through a literature review, the study draws on primary and secondary sources, including government documents, books, and scholarly journal articles. The findings indicate that the Agrarische Wet of 1870, through the principle of Domeinverklaring, systematically negated customary land rights and classified ulayat land as state property for agrarian exploitation during the Dutch colonial period. However, due to their small population and distinct socio-spatial patterns, the Baduy community largely escaped strict implementation of this policy, allowing them to retain de facto control over their customary territory. This condition persisted during the New Order era, when the recognition of customary law remained conditional and administratively limited. A significant paradigm shift occurred in the Reform era, particularly following decentralization and Constitutional Court Decision No. 35/PUU-X/2012, which redefined the Baduy as legal subjects entitled to de jure protection. Regional regulations, notably Lebak Regency Regulation No. 17/1990 and its subsequent amendments up to 2022, became key instruments for territorial delineation, customary protection, and human rights. Despite legal advancements, implementation continues to face structural and cultural challenges. This study underscores the urgency of strengthening sustainable protection of Baduy customary land rights.